Effective multidisciplinary approach for treatment of traumatized maxillary incisors and hypodontia. (1st January 2020) - Elhussein, Mustafa; O'Dwyer, Jonathan J; Sandler, Jonathan
Abstract : Fractured and missing teeth within the aesthetic zone have always posed a clinical challenge for the dental team. Management and treatment requires the input from a number of dental specialists to guarantee a high quality result. A case report is presented to demonstrate an effective combined orthodontic/restorative approach that fully restored aesthetics and function. The report is of a 14-year-old girl who traumatized her maxillary central incisors, in a dentition that was already compromised as she had congenital absence of her maxillary left lateral incisor. Using fixed orthodontic appliances, the fractured teeth were extruded to bring the fracture line above the level of the alveolar bone. This movement allowed an immediate aesthetic improvement, using stainless steel prefabricated posts and composite resin buildups, which also facilitated further orthodontic tooth movement. Teeth, that would otherwise have been extracted, were salvaged and, utilizing a multidisciplinary team approach, a reasonable long-term prognosis has resulted. CPD/Clinical Relevance: This case report aims to demonstrate how a multidisciplinary team approach in Orthodontics can be utilized for management of severely handicapped dentitions that have sustained dental injury. It is not the aim of this case report to discuss the treatment of dental injuries but to demonstrate and provide an overview of the possible treatment modalities that can be effective in restoring function and aesthetics, with special consideration given to missing teeth and subgingival crown fractures within the aesthetic zone.